Performance Management For Dummies - Aguinis, Herman (For Dummies, 2019)
Implement best-in-class performance management systems Performance Management For Dummies is the definitive guide to infuse performance management with your organization's strategic goals and priorities. It provides the nuts and bolts of how to define and measure performance in terms of what employees do (i.e., behaviors) and the outcome of what they do (i.e., results) - both for individual employees as well as teams. Inside, you'll find a new multi-step, cyclical process to help you keep track of your employees' work, identify where they need to improve and how, and ensure they're growing with the organization-and helping the organization succeed. Plus, it'll show managers to C-Suites how to use performance management not just as an evaluation tool but, just as importantly, to help employees grow and improve on an ongoing basis so they are capable and motivated to support the organization's strategic objectives. Understand if your performance management system is working Make fixes where needed Get performance evaluation forms, interview protocols, and scripts for feedback meetings Grasp why people make some businesses more successful than others Make performance management a useful rather than painful management tool Get ready to define performance, measure it, help employees improve it, and align employee performance with the strategic goals and priorities of your organization.